2004
DOI: 10.1099/vir.0.19317-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oncogenicity of Asian-American human papillomavirus 16 is associated with impaired E2 repression of E6/E7 oncogene transcription

Abstract: Asian-American (AA) variants of human papillomavirus 16 (HPV-16) are linked to a high incidence of cervical cancer in Mexico, with some evidence strongly suggesting that they are more oncogenic than European (E) variants, including their association with younger women and their higher associated risk of cervical cancer. Differences in the regulation of viral E6/E7 oncogene transcription by the E2 protein may be involved in the higher oncogenicity of AA variants. In E variants, E6/E7 oncogene transcription is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…More recently, it was suggested that in European variants the early E6/E7 gene transcription is repressed by the E2 protein and is frequently up-regulated by the interruption of the E2 gene during viral integration. In contrast, in tumor samples harboring Asian-American variants this gene was observed to be frequently retained (55). The association of Asian-American variants with retention of E1/E2 genes suggests that E2 nucleotide sequence variability could be an alternative mechanism up-regulating the expression of viral oncogenes.…”
Section: Nucleotide Variability and Oncogenic Potentialmentioning
confidence: 65%
“…More recently, it was suggested that in European variants the early E6/E7 gene transcription is repressed by the E2 protein and is frequently up-regulated by the interruption of the E2 gene during viral integration. In contrast, in tumor samples harboring Asian-American variants this gene was observed to be frequently retained (55). The association of Asian-American variants with retention of E1/E2 genes suggests that E2 nucleotide sequence variability could be an alternative mechanism up-regulating the expression of viral oncogenes.…”
Section: Nucleotide Variability and Oncogenic Potentialmentioning
confidence: 65%
“…In Asian-American variants the E2 gene is usually retained in tumor samples suggesting that variability in this gene could be a mechanism of upregulating the transcription of early oncogenes. 44 It has also been observed that replication efficiency is higher among Asian-American as compared to European variants of HPV-16. 45,46 The efficient E1/ E2 expression and elevated viral replication during persistent infection could confer to variants from the Asian-American branch the enhanced oncogenic potential reported in some epidemiological studies.…”
Section: Discussionmentioning
confidence: 94%
“…Direct in vitro evidence regarding differences in biologic properties between HPV31 variants has not been available. However, the variable biologic properties of HPV16 and HPV18 variants were demonstrated by studies in vitro, [30][31][32][33] showing that the variants of these types differed in their abilities to induce p53 degradation, keratinocyte differentiation, transcription of E6/E7 oncogenes and tumor formation. It is likely that some nucleotide alterations may work individually or jointly to alter the variants' oncogenic potentials and be responsible for the observed risk differences.…”
Section: Discussionmentioning
confidence: 99%